Karakteristik Air Gambut Di Rimbo Panjang Kab. Kampar Sebagai Bahan Baku Air Minum - Muhammad Al- Hafizd; David Andrio; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Peat water has high color intensity, low pH, high levels of organic matter, turbidity and low suspended particle content and low cation content. Peat water test results produce high levels of color and organic matter parameters in peat water. Where, a high level of parameters can cause problems caused by consuming peat water without treatment including making teeth brittle due to acidic water. And peat water also contains organic or inorganic substances that can disrupt the body's metabolism. Keywords: Activated Carbon, Alum, Color, Organic matte, Peat Water